Natural and anthropogenic dynamics of the coastal environment in northwestern Corsica (western Mediterranean) over the past six millennia. (15th February 2022) - Di Rita, Federico; Ghilardi, Matthieu; Fagel, Nathalie; Vacchi, Matteo; Warichet, François; Delanghe, Doriane; Sicurani, Jean; Martinet, Lauriane; Robresco, Sébastien
Abstract: The present paper provides new insights into the climatic and anthropic factors that influenced a 6000-year coastal evolution in northwestern Corsica, the third largest island of the western Mediterranean. Pollen, microcharcoal, sedimentary and geochemical analyses were carried out on a core drilled in the Crovani coastal wetland to reconstruct the regional drivers of landscape change. We show that anthropogenic and climate-induced fires favoured the development of Mediterranean maquis, dominated by Erica and Quercus ilex, from ca. 6000 to 3350 cal. BP. A change in arboreal vegetation triggered a short but intense sediment input in the Crovani pond between ca. 3350 and 3200 cal. BP. This is consistent with a coeval process of runoff recorded in several coastal sites of western Corsica and related to an arid climate change occurred in many sites of the western Mediterranean around 3200 years ago. We provide evidence of agriculture during the Late Neolithic from ca. 3900 BC, which is much earlier than any archaeological evidence previously available in this area of Corsica, followed by a progressive decline of arable farming practices. Human impact has been responsible for a degradation of the maquis only from approximately 3000 cal. BP, and it intensified in Roman times, when the area experienced the first phase of galena exploitation from the Argentella mines. Over the last 500 years, the present work evidences a major development of Castanea related to cultivation during the Genoese administration of Corsica. Our findings suggest that solar activity and the North Atlantic Oscillation had an influence on centennial-scale forest cover variations during the last 6000 years. Highlights: A new palynological, sedimentological and geochemical study is presented from a coastal wetland of Corsica. The high-resolution 6000-year pollen record shows an unprecedented long persistence of Erica and Quercus ilex maquis. Human activities developed especially during the Late and Final Neolithic and the last 1000 years. Evidence of agriculture predates any Neolithic archaeological findings in this region. The 4.2 ka event, Homeric Minimum, and Little Ice Age are not associated with forest declines.